Development Strategy for Trigona leaviceps Honey Bee Cultivation in Sait Buttu Saribu Village, Pamatang Sidamanik District, Simalungun Regency - Sihombing, Benteng H; Nurrachmania, Meylida; Fadilah, Endah Ayu (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
The target of the research is to find out the existing conditions of honey bee cultivation business management and to determine the management strategy set based on existing conditions of TAKOMA Farmer Groups in Sait Buttu Saribu, Sidamanik District, Simalungun Regency. The data retrieved is primary data and secondary data. Through direct interviews using questionnaires of 17 honey bee farmers, primary data were obtained As for the secondary data obtained from literaure. Research analysis, namely descriptive analysis using SWOT analysis techniques. The existing condition of managing the honey bee cultivation business of the TAKOMA Farmer Group is that the business has high strength so that it runs well, does not have any significant weaknesses from the internal aspect, has taken advantage of opportunities from external factors aimed at improving cultivation efforts, and experiencing meaningful threats that can be improved from the aspect of work resilience. The strategy set in the framework of business development is to maintain and maintain the internal strengths owned and make good use of the opportunities that are already owned and also suppressing as small as possible the threats that can cause the failure of the TAKOMA farmer group's honey bee cultivation development efforts.